Cecal Lipoma Presenting as Acute Intestinal Obstruction in an Elderly Woman: A Case Report. (20th June 2013) - Kastanakis, Miltiades; Anyfantakis, Dimitrios; Symvoulakis, Emmanouil K.; Katsougris, Nikolaos; Papadomichelakis, Alexandros; Kokkinos, Ioannis; Petrakis, George; Bobolakis, Emmanouil
Abstract : Colonic lipomas are rare nonepithelial tumors that are usually detected incidentally during surgery or colonoscopy. Although lipomas generally remain asymptomatic, when they exceed 2 cm of diameter they may cause abdominal pain, obstruction, or intussusception. Here we present a case of an elderly woman referred by her general practitioner to a general hospital of Crete because of acute abdominal pain along with signs of intestinal obstruction and a positive history of appetite loss. Abdominal computed tomography was performed. To marginalise the risk of malignancy, a right hemicolectomy was performed. Histopathological examination of the resected specimen confirmed the diagnosis of cecal lipoma.